1983
DOI: 10.1002/1098-108x(198321)2:3<93::aid-eat2260020309>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Attrition in a behavioral weight-control program: A comparison of dropouts and completers

Abstract: A major problem in weight‐reduction programs is that a significant number of individuals terminate treatment prematurely. To help alleviate some of the problems associated with high attrition, it is important to understand the ways in which treatment dropouts are different from those individuals who complete a weight‐reduction program. In the present study 271 obese persons who participated in a Health Maintenance Organization's low‐cost behavioral program were evaluated. At the end of the 12‐session program, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Homogeneity in the sample may also explain why age, gender, or dieting history did not predict attrition in the present study. This is in contrast with previous studies , although similar null results have been reported by others for gender (e.g., ), age (e.g., ), and previous dieting attempts . We observed a somewhat higher level of education among program completers, which is in line with previous findings .…”
Section: Discussionsupporting
confidence: 78%
“…Homogeneity in the sample may also explain why age, gender, or dieting history did not predict attrition in the present study. This is in contrast with previous studies , although similar null results have been reported by others for gender (e.g., ), age (e.g., ), and previous dieting attempts . We observed a somewhat higher level of education among program completers, which is in line with previous findings .…”
Section: Discussionsupporting
confidence: 78%
“…Attrition can also jeopardise the effectiveness and cost-effectiveness of a treatment program, with increased administrative costs and the underutilisation of available resources being major issues [5,12,[34][35][36]. As attrition is associated with poorer outcomes for individual participants [2,29], retaining participants is also crucial in improving outcomes in weight-management programs overall.…”
Section: The Impact Of Attritionmentioning
confidence: 81%
“…Thirty-three studies considered the relationship between age and attrition. Seventeen studies failed to demonstrate a relationship (3,4,(13)(14)(15)20,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and 13 studies found that younger age was associated with higher attrition (2,7,22,23,26,(39)(40)(41)(42)(43)(44)(45)(46). Only two studies found that older patients were more likely to drop out of treatment (47,48) and these studies involved very small sample sizes (n = 39 and 49, respectively).…”
Section: Demographic Variablesmentioning
confidence: 99%